Tingkat Kepedulian Masyarakat Dalam Menjaga Budaya Hidup Bersih di Kenagarian Palangki Kecamatan IV Nagari Kabupaten Sijunjung - Masnah, Pera; Erita, Yeni; Nefilinda, Nefilinda (STKIP PGRI Sumbar, 2013)
This study aims to find out the opinions Concern In Caring Community Clean Living Culture in Kenagarian Palangki District IV District SIJUNJUNG Nagari. This kind of research is descriptive. Population in this study was the whole family heads in Kenagarian Palangki totaling 911 family heads. Study samples were collected with proportionate Random Sampling techniques, with samples of 10% until the sample totaled 91 KK. Results of the research found that: (1) discipline community about clean living culture in Kenagarian Palangki District IV includes bad Nagari average score of 2.03 and 50.96% of respondents access level, (2) The role of the community about clean living culture of within the District IV Nagari Palangki Kenagarian including poor with average score 2.48 and 62.0% of respondents access level. (3) The behavior of the community about clean living culture on the environment in Kenagarian Palangki District IV Nagari including poor average score of 2.41 and 60.49% of respondents access level. Recommended to the community to better implement and improve the environment and the discipline to follow and role in the cultural life clean, and behaviour well towards the environment.